1977
DOI: 10.1172/jci108772
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between High Density and Low Density Lipoproteins during Uptake and Degradation by Cultured Human Fibroblasts

Abstract: A B S T RA CT High density lipoprotein (HDL) inhibited the binding (trypsin-releasable radioactivity), internalization (cell-associated radioactivity after trypsinization), and degradation (TCA-soluble noniodide radioactivity) of 1251-low density lipoprotein (1251-LDL) by cultured normal human fibroblasts. At HDL:LDL molar ratios of 25:1 (protein ratios about 5:1), these parameters were reduced by about 25%. Unlabeled LDL was about 25 times more effective in reducing 125I-LDL binding, implying that if HDL and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…Recent studies have demonstrated that HDL can bind to high-affinity sites on cells from a variety of different tissues, including rat adrenal gland (2, 3), rat testes (4), rat and canine liver (23)(24)(25)(26), bovine endothelium (25), and human skin fibroblasts (6,28,29). The physiological significance of this HDL binding has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that HDL can bind to high-affinity sites on cells from a variety of different tissues, including rat adrenal gland (2, 3), rat testes (4), rat and canine liver (23)(24)(25)(26), bovine endothelium (25), and human skin fibroblasts (6,28,29). The physiological significance of this HDL binding has yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of the postmitochondrial supernatant fraction and assay of HMG CoA reductase activity were performed as described by Brown et al (33) (36).…”
Section: Methodsmentioning
confidence: 99%
“…4). Intravenous injection of sterile saline into heavily infected mice (5 X 108 trypanosomes per ml of blood at 0 time) had no effect on the rising parasitemia: by 15 hr after injection, trypanosomes were too numerous to count accurately and by 19 Standard in vitro incubation conditions were used. HDL was prepared by two cycles of ultracentrifugal flotation and was concentrated roughly 9-fold relative to the original serum from which it was prepared.…”
Section: Methodsmentioning
confidence: 99%